Contextual Teaching and Learning: An Alternative Method to Teach Speaking - Widodo, Urip (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2020)
Speaking is one of problems facing by EFL students. An effective method of teaching speaking will guide the EFL students to gain the better speaking ability. The Objective of this research is to know whether the contextual teaching and learning is better than audio-lingual method to teach speaking. This experimental research was carried out in the vocational school. The number of population was four classes (110 students) that consisted of eleventh grade A,B,C, and D. The sample were the eleventh grade A as the experimental group and B as the control group. Each group consisted of 30 students. The experimental group was taught by using Contextual Teaching and Learning, while the control group was taught by using Audio-Lingual Method. The data collection technique was through speaking test and data analysis technique was through descriptive statistic and inferential. Based on the data analysis shows that the mean score of the students who were taught by using contextual teaching and learning is 80,93 while the mean score of the students who were taught by using audio-lingual method is 76,33. Moreover, the Fo (6,64) is higher than Ft (4,00) at the level of significance Î±= 0,05 which means the null hypotheses is rejected and the alternative hypotheses is accepted. As a conclusion contextual teaching and learning is more effective than audio-lingual method to teach speaking.